Kebijakan Wisata Halal (Halal Tourism) Berbasis Kearifan Lokal di Kabupaten Lima Puluh Kota - Novianti Monyca; Muslim Muslim (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2026)
This study examines the development of halal tourism based on local wisdom in Lima Puluh Kota Regency, focusing on the Harau Valley area as a leading destination. The research aims to analyze halal tourism development and identify challenges faced in its implementation. The study employs a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation studies. Research informants include the Department of Tourism, Youth and Sports, the Ministry of Religious Affairs, the Minangkabau Indigenous Leadership Council, Tourism Awareness Groups, business operators, and tourists. Data analysis uses the Miles and Huberman interactive model. The results show that halal tourism development in Harau Valley has great potential supported by natural compatibility with sharia principles, the philosophy of "Adat Basandi Syarak, Syarak Basandi Kitabullah," and strong cultural attractions. However, significant challenges remain, including limited infrastructure, low halal certification in accommodation and culinary sectors, limited human resource capacity, suboptimal promotion, weak inter-agency coordination, and funding constraints. The study recommends strengthening district-level halal tourism regulations, intensifying halal certification socialization, enhancing human resource capacity through continuous training, developing integrated digital promotion systems, and strengthening multi-stakeholder coordination in sustainable halal tourism development.